Nickeliferous pyrite tracks pervasive hydrothermal alteration in Martian regolith breccia: A study in NWA 7533. (20th November 2015) - Lorand, Jean‐Pierre; Hewins, Roger H.; Remusat, Laurent; Zanda, Brigitte; Pont, Sylvain; Leroux, Hugues; Marinova, Maya; Jacob, Damien; Humayun, Munir; Nemchin, Alexander; Grange, Marion; Kennedy, Allen; et al.
Abstract: Martian regolith breccia NWA 7533 (and the seven paired samples) is unique among Martian meteorites in showing accessory pyrite (up to 1% by weight). Pyrite is a late mineral, crystallized after the final assembly of the breccia. It is present in all of the lithologies, i.e., the fine‐grained matrix (ICM), clast‐laden impact melt rocks (CLIMR), melt spherules, microbasalts, lithic clasts, and mineral clasts, all lacking magmatic sulfides due to degassing. Pyrite crystals show combinations of cubes, truncated cubes, and octahedra. Polycrystalline clusters can reach 200 μm in maximum dimensions. Regardless of their shape, pyrite crystals display evidence of very weak shock metamorphism such as planar features, fracture networks, and disruption into subgrains. The late fracture systems acted as preferential pathways for partial replacement of pyrite by iron oxyhydroxides interpreted as resulting from hot desert terrestrial alteration. The distribution and shape of pyrite crystals argue for growth at moderate to low growth rate from just‐saturated near neutral (6 < pH<10), H2 S‐HS‐rich fluids at minimum log f O2 of >FMQ + 2 log units. It is inferred from the maximum Ni contents (4.5 wt%) that pyrite started crystallizing at 400–500 °C, during or shortly after a short‐duration, relatively low temperature, thermal event that lithified and sintered the regolith breccias, 1.4 Ga ago as deduced from disturbance in several isotope systematics.